Creativity and unnaturalness in the use of phrasal verbs in ESL learner language - Zarifi, Abdolvahed; Jayakaran Mukundan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Interest in ESL learner language has gained momentum since the 1990s with the generation of learner corpora, development of robust Concordance software and the establishment of the principles of the corpus –-linguistic methodology. All these innovations have empowered researchers to investigate not only the frequent but also the idiosyncratic features of different language phenomena in learner language. This corpus-based content analysis stydy was an attempt to explore the phenomena of creativity and unnaturalness in the use of phrasal verbs in an ESL context. Findings revealed that albeit the ESL learners were competent enough in creating compositional phrasal verbs, hence creative, they often produced unusual forms in their attempt to use and create idiomatic phrasal verbs. Materials developers and teachers are, therefore, recommended to provide materials and learning activities that would enable ESL learners to more effectively acquire phrasal verbs in general and idiomatic combinations in particular.